1996
DOI: 10.1088/0022-3727/29/10/018
|View full text |Cite
|
Sign up to set email alerts
|

The drift velocity and longitudinal diffusion coefficient of electrons in nitrogen and carbon dioxide from 20 to 1000 Td

Abstract: The distribution of arrival time spectra (ATS) of electrons in nitrogen and carbon dioxide has been measured over the range of E/N from 20 to 1000 Td (1 ) at room temperature by a double-shutter drift tube. The drift velocity of electrons in and was evaluated from these distributions by the ATS method. Moreover, the ratio of the longitudinal diffusion coefficient to the electron mobility was measured. The values of and in and were in good agreement with experimental and theoretical values obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
41
0
5

Year Published

1998
1998
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 15 publications
7
41
0
5
Order By: Relevance
“…4 The drift velocity, W m , is deduced by dividing the mean time of arrival of electrons by the distance between the electrodes. The experimental apparatus and procedure for the ATS method were the same as those described by Hasegawa et al 5 In the present study, the position of the collector plate was set at four locations, and the final value of drift velocity was determined by averaging the values determined at the four cases for each value of E/N.…”
Section: Experimental Methods a Arrival-time Spectra Methodsmentioning
confidence: 99%
“…4 The drift velocity, W m , is deduced by dividing the mean time of arrival of electrons by the distance between the electrodes. The experimental apparatus and procedure for the ATS method were the same as those described by Hasegawa et al 5 In the present study, the position of the collector plate was set at four locations, and the final value of drift velocity was determined by averaging the values determined at the four cases for each value of E/N.…”
Section: Experimental Methods a Arrival-time Spectra Methodsmentioning
confidence: 99%
“…The experiment is conducted using a double-shutter drift tube, where arriving electrons are collected by the electrode with shutter 2 at a certain distance from the cathode ͑with shutter 1 releasing initial electrons͒. The experimental apparatus and procedure for this method are the same as those described by Hasegawa et al 11 The value W m is determined by the derivative of the mean arrival-time ͗t͘ with respect to the drift distance as in Eq. ͑3͒.…”
mentioning
confidence: 99%
“…The experimental apparatus used in the present experiment is the same as that for the ATS method described by Hasegawa et al, 8 but is utilized differently, where the double-shutter is moved little by little along the field direction in the drift chamber for capturing the spatial distribution of electron swarms. Figure 1 shows a schematic diagram of the chamber and its internal configurations.…”
Section: A Double-shutter Electrode In Drift Tubementioning
confidence: 99%
“…The authors have measured the arrival-time distribution of electrons by a double-shutter electrode technique based on the ATS method, 8,9 demonstrating the ATS method experimentally in order to achieve a direct comparison of the parameters between the theoretical and experimental. In the course of the ATS measurement, we found that our apparatus enables us to measure also the spatial distribution of an isolated swarm under moderate field conditions ͑see next section͒ by moving the double-shutter electrode to collect incoming electrons along the drift direction ͑electric field direction͒ and to deduce directly a typical parameter, the drift velocity.…”
Section: Introductionmentioning
confidence: 99%